'Avant-garde' art groups in China, 1979-1989 : the stars - the Northern Art Group - the Pond Association - Xiamen Dada : a critical polylogue /: the stars - the Northern Art Group - the Pond Association - Xiamen Dada : a critical polylogue. (2013) - Gladston, Paul
No abstract available